Modified asphalt binders: A bibliographic analysis (Research, Society and Development, 2021)
The application of modified asphalt binders on road pavements has grown steadily in recent decades. This fact is justified by several reasons such as the advent of the great advance of the chemical industries, the consecration of the use of polymeric materials in reinforcement works and several advantages that arise from these facts such as economy, safety, durability, among others. In this theme, the present work aims to carry out a bibliographic review addressing the main researches on modified asphalt binders.